Bradykinin B2 receptor antagonist icatibant reduces inhibitory effect of captopril on growth of cultured neonatal rat cardiomyocytes - Lei Bei-Lei; Guo Zhao-Gui (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study whether endogenous kinins are negative modulators in the growth of cardiomyocytes and their possible cellular and molecular mechanisms. METHODS: Cultured neonatal rat cardiomyocytes were used. Intracellular RNA and protein synthesis were measured by [3H]uridine incorporation and [3H]leucine incorporation, respectively. The expression level of proto-oncogene c-myc, c-fos mRNA was observed by Northern blotting. RESULTS: Exposure of cardiomyocytes to captopril (Cap, 100 mumol.L-1) for 48 h inhibited the rates of [3H]Urd and [3H]Leu incorporations by 25% and 26%, respectively, and for 2 h inhibited c-myc, c-fos mRNA expression by 75% and 55%, respectively. Treatment of angiotensin II (Ang II, 1 mumol.L-1) for 48 h significantly increased the rates of [3H]Urd and [3H]Leu incorporations and for 1 h induced c-myc, c-fos mRNA overexpression, which were reduced by pretreatment with Cap (100 mumol.L-1). Icatibant acetate (Hoe 140, a specific antagonist of bradykinin B2 receptor) 0.1-10 mumol.L-1 blocked the effects of Cap in a concentration-dependent manner. CONCLUSION: Endogenous kinins exhibited a negative modulatory effect on growth of cardiomyoctes via BK B2 receptor.